Pengaruh PAD, DAU, DAK, dan Belanja Modal terhadap PDRB Dan Hubungannya dengan Kemiskinan di Kota Jambi - Ferry Risnu Murti, Ferry Risnu Murti; Tan, Syamsurijal; Zulfanetti, Zulfanetti (Jurnal Paradigma Ekonomika, 2023)
The purpose of this study is to describe the effect of PAD, DAU, DAK and Capital Expenditure on GRDP in Jambi City for the 2000-2020 period, either partially or simultaneously, as well as the relationship between GRDP and poverty in Jambi City for the 2000-2020 period. This study uses quantitative methods, where the data sources in this study are regional financial and asset management agency of Jambi City, regional revenue and retribution management agency of Jambi City, and Jambi City Statistical Center. The data obtained were then analyzed using quantitative analysis techniques in the form of multiple linear regression analysis and product moment correlation analysis. The results of the statistical t test prove that partially PAD and DAK have a significant effect on Jambi City's GRDP for the 2000-2020 period, while DAU and capital expenditures have no significant effect on Jambi City's GRDP for the 2000-2020 period. The results of the F test prove that simultaneously PAD, DAU, DAK and Capital Expenditures have a significant effect on Jambi City's GDP for the 2000-2020 period. The correlation test results show that GRDP has a significant relationship with poverty in Jambi City for the 2000-2020 period. Based on these findings, it is suggested that local governments can explore sources of Regional Original Income (PAD) either by intensification or extensification, as well as manage both DAU and DAK so that the increase in GRDP each period can be achieved optimally and on target. Â